Painless ulcers and fissures of toes: Hereditary sensory neuropathy, not leprosy - Angoori Gnaneshwar Rao (Wolters Kluwer Medknow Publications, 2016)
Hereditary sensory neuropathies (HSN) are rare genetically determined neuropathies. They often manifest as painless injuries in children. We present HSN in a 5-year-old boy who presented with recurrent fissuring and ulceration involving both great toes.